Pengaruh Minat Belajar dan Perhatian Orang Tua Terhadap Hasil Belajar Ekonomi Siswa Pada Pembelajaran Daring di SMA N 59 Jakarta - Muthmaina, Karima; S, Armida (Jurnal Salingka Nagari, 2023)
This study aims to determine the effect of learning interest and parent attention on economic student achievement in online learning at SMA N 59 Jakarta. This type of research is descriptive quantitative using SPSS version 25. The instruments used in this study were quesitionnaires and research documentation. The population of this study was 105 students with a sample of 84 students through proportional random sampling. The data analysis technique used in this research is multiple linear regression. The results showed that: (1) learning interest and parent attention had a positive and significant effect on economic student achievement in online learning at SMA N 59 Jakarta, (2) learning interest had an effect positive and significant effect on economic student achievement in online learning at SMA N 59 Jakarta, and (3) parent attention has no positive and significant effect on economic student achievement in online learning at SMA N 59 jakarta. Suggestion for students to always increase learning interest related to economic subject in online learning. For parent to pay more attention to online learning, especially to provide guidance and motivation.